Exploring Co-Regulation-Related Factors in the Mothers of ADHD Children-Proof of Concept Study - Ruth Yaacoby-Vakrat; Margalit Pade; Tami Bar-Shalita (MDPI AG, 2023)
Background: Attention deficit hyperactivity disorder (ADHD) is a complex neurological condition interfering with family relationships and co-regulation capabilities. Therefore, exploring factors underpinning parental co-regulation ability is crucial for future fostering relationships in families of children with ADHD. Objective: This preliminary study aims to characterize and compare the executive-functions, anxiety, self-efficacy, and sensory modulation in mothers of children with and without ADHD. Method: Mothers of children with (study group) and without (control-comparison, group) ADHD completed online self-reports, measuring executive-functions; parental self-efficacy; anxiety; and sensory modulation. Results: The study group (N = 40) had lower self-efficacy compared to the control group (N = 27; p = 0.018), and the control group had lower sensory responsiveness (p = 0.025). Within both groups the Behavior Rating Inventory of Executive Function-Adult (BRIEF-A) Global Executive Function Composite score (GEC) and the Beck Anxiety Inventory (BAI) were moderately correlated. Further, within the study group correlations were found between the BRIEF-A-GEC and the Sensory Responsiveness Questionnaire (SRQ)-Aversive scores (r = 0.37, p ≤ 0.01), and between the BRIEF-A Behavioral-Rating-Index and the parental self-efficacy scores (r = 0.31, p ≤ 0.05). Within the control group, negative correlations were found between the BRIEF-A-GEC and SRQ-Hedonic scores (r= −0.44, p < 0.05). Conclusion: Self-efficacy, executive-functions, high sensory responsiveness and anxiety traits are interwoven and may impact parental co-regulation ability.